Do Classical Studies Open your Mind? - Giorgio Brunello; Piero Esposito; Lorenzo Rocco; Sergio Scicchitano (Global Labor Organization (GLO), 2023)
We investigate whether classical studies in high school - that emphasize in Italy the study of ancient languages such as Latin and Greek - affect personality traits. Using Italian survey data, we compare individuals who did classical studies in high school with similar individuals who completed a more scientific academic curriculum. We find that having done classical studies does not affect conscientiousness and openness but increases neuroticism and self-reported unhappiness.
Keywords: I21; I26; 330; school choice; education; classical studies; Big-5; non-cognitive skills; personality traits